2012
DOI: 10.1172/jci61758
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic T cell–APC interactions sustain chronic inflammation in atherosclerosis

Abstract: Atherosclerosis is a chronic inflammatory disease of large and medium-sized arteries characterized by leukocyte accumulation in the vessel wall. Both innate and adaptive immune responses contribute to atherogenesis, but the identity of atherosclerosis-relevant antigens and the role of antigen presentation in this disease remain poorly characterized. We developed live-cell imaging of explanted aortas to compare the behavior and role of APCs in normal and atherosclerotic mice. We found that CD4 + T cells were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
237
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(261 citation statements)
references
References 82 publications
19
237
0
5
Order By: Relevance
“…For example, is DC-mediated T cell activation occurring in draining lymph nodes, followed by T cell homing to lesions, or might there also be DC/T cell activation occurring in the lesions themselves? A recent study demonstrated productive interaction of CD4 + T cells with CD11c hi cells in the vascular wall of atherosclerotic lesions ex vivo, suggesting that lesional CD11c hi DCs could activate T cells in the atherosclerotic lesions in vivo (19). In this context, we observed decreased Treg numbers not only in aorta-draining iliac and mediastinal lymph nodes of Cre + mice, but also in the nondraining inguinal lymph nodes (Supplemental Figure 11).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…For example, is DC-mediated T cell activation occurring in draining lymph nodes, followed by T cell homing to lesions, or might there also be DC/T cell activation occurring in the lesions themselves? A recent study demonstrated productive interaction of CD4 + T cells with CD11c hi cells in the vascular wall of atherosclerotic lesions ex vivo, suggesting that lesional CD11c hi DCs could activate T cells in the atherosclerotic lesions in vivo (19). In this context, we observed decreased Treg numbers not only in aorta-draining iliac and mediastinal lymph nodes of Cre + mice, but also in the nondraining inguinal lymph nodes (Supplemental Figure 11).…”
Section: Discussionsupporting
confidence: 65%
“…One hypothesis for the presence of activated T cells in atherosclerotic lesions is DC-mediated presentation of antigens to T cells in peripheral lymph nodes and perhaps the lesions themselves (5,19). As shown in Figure 2A, analysis of aorta-draining iliac lymph nodes demonstrated that the naive/effector T cell ratio was significantly higher in the Cre + mice and the percentage of Tregs was lower, while the total T cell numbers were unaffected (data not shown).…”
Section: Cd11c-myd88 Deficiency Suppresses DC Maturation and T Cell Amentioning
confidence: 90%
“…Although proatherogenic T cell responses could plausibly occur in any secondary lymphoid tissue, effector T cells must migrate into the arterial wall and be locally activated by APCs to influence lesion development. Both DCs and lesional macrophages, including cholesterol-loaded foam cells (130,131), likely participate in the local activation of effector CD4 + and CD8 + T cells. In addition, stimulation of plasmacytoid DCs also plays an atherogenic role (132).…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsesmentioning
confidence: 99%
“…Development of atherosclerotic plaque is driven by dynamic interactions among the lipid milieu, fluid shear forces, cells of the vascular wall, and cells recruited from the circulation. Endothelial cells, monocytes, T cells, and platelets have all been implicated in atherogenesis (2)(3)(4). Recent studies have described the role of platelet activation in the early stages of atherogenesis via transient endothelial and mononuclear interactions and in situ release of mitogens and chemoattractants (5,6).…”
Section: Introductionmentioning
confidence: 99%